Increased susceptibility to acetylcholine in the entorhinal cortex of pilocarpine-treated rats involves alterations in KCNQ channels - Maslarova, Anna; Salar, Seda; Lapilover, Ezequiel; Friedman, Alon; Veh, Ruediger W.; Heinemann, Uwe (Neurobiology of Disease, 2013)
In models of temporal lobe epilepsy, in-vitro exposure of the entorhinal cortex (EC) to low concentrations of acetylcholine (ACh) induces muscarinic-dependent seizure-like events. Potassium channels from the KCNQ/Kv7 family, which close upon activation of muscarinic receptors, are mutated in several epileptic syndromes such as benign familial neonatal convulsions (KCNQ2/KCNQ3) and sudden unexplained death in epilepsy (KCNQ1). Therefore, we tested the hypothesis whether the ictogenic effect of ACh involves alterations of KCNQ channels. In horizontal temporo-hippocampal slices from pilocarpine-treated chronically epileptic rats, field potential recordings of epileptiform activity were performed in response to the application of ACh, the KCNQ blocker linopirdine, and KCNQ agonists. In the EC of control rats, ACh (20 and 50. μM) induced nested fast activity in the range of 15-20. Hz riding on <. 1. Hz slow oscillations. By contrast, in slices from pilocarpine-treated rats, 5. μM ACh was sufficient to induce interictal discharges that frequently transformed to epileptiform events at 20. μM ACh. While the non-specific KCNQ/Kv7 channel blocker linopirdine (20 and 50. μM) had no effect in control animals, in slices from epileptic rats it induced interictal discharges or seizure-like events. These could be blocked by the unspecific KCNQ/Kv7 agonist retigabine and attenuated by the Kv7.1 agonist L364-373. Immunohistochemistry revealed reduced expression of KCNQ2 and KCNQ3 in the EC and of KCNQ3-positive dendrites in the subiculum of epileptic rats. These results indicate that channels of the KCNQ family are key regulators of seizure susceptibility and their decreased availability in the epileptic tissue may reduce seizure threshold and contribute to ictogenesis. © 2013 Elsevier Inc.
Created from Fastlane, Scopus look-up
Keywords: Acetylcholine; Entorhinal cortex; KCNQ potassium channels; Linopirdine; M-current; Temporal lobe epilepsy